Development of students' professional interests based on an innovative approach (Journal of Pedagogical Inventions and Practices, 2023)
In modern innovative conditions, the result of a conscious choice of a profession by students of a general education school should not be narrowly focused professional specializations, but the ability of a student to strive for professional self-improvement throughout his life, independently set goals and organize steps to achieve them.